Penerapan SHERPA untuk Identifikasi Kinerja dan Human Error Pengoperasian Mesin Induk Kapal Penangkap Ikan - Yaqin, Rizqi Ilmal; Septianda, Devin; Priharanto, Yuniar Endri; Abrori, M. Zaki Latif (Jurnal Rekayasa Sistem Industri, 2024)
Occupational accidents due to human errors in the operation of main engines on fishing vessels need to be considered because they can be fatal to the ship. This study aims to identify and analyze critical activities in the operation of fishing vessel main engines using the Systematic Human Error Reduction And Prediction Approach (SHERPA) method. The analytical method is to collect data by observation and interviews to fulfill the SHERPA tabulation. SHERPA analysis is closely related to using Hierarchial Task Analysis (HTA) diagrams to determine the amount of activity generated in the operation of fishing vessel main engines. In addition, work intensity analysis is applied to determine the stages that need to be considered in the operation of the main engine. Based on the resulting analysis, the highest work intensity is at the operating stage of the main engine. At the same time, the critical activity level is in closing the fuel faucet and the cooling system water faucet, which are included in the activity category of turning off the main engine. The findings of this study provide insight into handling critical activities in the operation of the main engine so that a strategy is needed to reduce human error in operation. The strategy for reducing this activity is strictly supervising and modifying or adding tools to make it easier for operators. The investigation results can inform the intensity and critical points of human error in the operation of fishing vessel main engines to reduce the occurrence of work accidents.